Effect of Multimorbidity on Depression of Indonesian Older Persons: An Application of the Utility Function - Farma Mangunsong; Theerathorn Yoongthong; Rina Gustiana (International Journal of Economics Development Research (IJEDR), 2026)
Previous studies have found adverse relationships between physical deterioration and depression among older persons. Relied on the utility function, this study assumed that living in good health condition and at an older age contribute to higher utility. To assess the causal relationship, it used longitudinal panel data of older adults withdrawn from three waves of the Indonesian Family Life Survey (IFLS) waves 3, 4, and 5. Good health status and higher utility were represented by fewer morbidities and lower depression, respectively. By applying the Robust Hausman test (p-value 0.3903), the Random Effect (RE) Model is more appropriate than the Fixed Effect (FE) Model. The RE Model suggests that more morbidities and being older cause higher depression. Meanwhile, older persons living in urban areas tend to have lower depression than those in rural areas. Promotion of mental health services for Indonesian older persons and utilization of the national health insurance are important for older persons to mitigate the adverse effects of multimorbidity.